Factors Affecting Wus' Interest In Iva Examination At Uptd Sukatani Puskesmas - Yoanita; Wintarsih; Melisa Putri Rahmadhena; Lili Anggraiani (Journal of Innovative and Creativity, 2025)
Reproductive health is a state of complete physical, mental, and social well-being and not merely the absence of disease or disability in all matters relating to the reproductive system, functions and processes. ervical Cancer is a malignant tumor that grows in the cervix (the lowest part of the uterus attached to the top of the vagina). IVA is a visual test using a solution of acetic acid (2% acetic acid) and lugol's iodine solution on the cervix and observing the color changes that occur after the application.To determine the factors that influence women's interest in IVA examination at the Sukatani Health Center UPTD in 2023. This type of research uses an analytical research method using a cross-sectional design. The population in this study were 482 women of childbearing age aged 30-50 years in the July period at the Sukatani Health Center UPTD, the number of samples was 83 respondents. Bivariate analysis using the chi-square test. Almost all women of childbearing age have moderate interest in IVA examination with a percentage of 81.9%. Most women of childbearing age have a negative attitude towards IVA examination with a percentage of 62.7%. Most women of childbearing age have a percentage of 65.1%. Most women of childbearing age have husband support that supports IVA examination with a percentage of 53.0%. Most women of childbearing age have support from health workers that supports IVA examination with a percentage of 55.4%. It can be concluded that there is a relationship between attitudes, husband's support, support from health workers with the interest of women of childbearing age in IVA examination at the Sukatani Health Center UPTD in 2023 with P = < 0.05. There is no relationship between education and the interest of women of childbearing age in IVA examination at the Sukatani Health Center UPTD in 2023 with P = > 0.05.